Sarcopenia from Pathophysiology to Clinical : Literature Review - Hidayat, Rachmat; Nur Riviati (Fakultas Kedokteran Universitas Sriwijaya (Faculty of Medicine, Universitas Sriwijaya) Indonesia, 2021)
A B S T R A C TThe causes of sarcopenia are thought to be multifactorial including: environmentalfactors, illness, activation of inflammatory pathways, mitochondrial dysfunction, lossof neuromuscular junctions, reduced number of satellite cells and changes in thequality of hormonal function. The mechanism of sarcopenia occurs because the agingprocess coupled with reduced physical activity can cause the formation of cytokinesto increase so that inflammation is easy, insulin resistant, anabolic resistance andneuromuscular impairments.